Human Blood Circular System Educational Digital Comics for Improving Learning Outcomes - Ananda Aisyah; Deni Setiawan (Postgraduate, University of Mataram, 2023)
The learning outcomes of class V at SDN Bendungan Semarang in science subjects on the human circulatory system are low. The average learning outcome of fifth-grade students at SDN Bendungan is 63, where the score is less than the standard of minimum value for science subjects, namely 75. This study aims to develop the learning media